STEM-11. HYDROGEN SULFIDE FUNCTIONS AS A TUMOR SUPPRESSION IN GLIOBLASTOMA. (12th November 2021) - Silver, Daniel J; Roversi, Gustavo; Bithi, Nazmin; Wang, Sabrina; Troike, Katie M; Neumann, Chase K; Ahuja, Grace; Reizes, Ofer; Brown, J Mark; Hine, Christopher; Lathia, Justin
Abstract: Glioblastoma (GBM) cancer stem cells (CSCs) respond to a variety of stimuli within their immediate surroundings. However, little is known about the lifestyle factors that alter CSC enrichment and function within the tumor microenvironment (TME). To examine the consequences of diet-induced obesity on the progression of GBM, we interrogated tumor growth using patient-derived and syngeneic GBM models implanted into the brains of mice fed either an obesogenic high-fat diet (HFD) or a low-fat, control diet. HFD consumption resulted in an accelerated disease trajectory, presenting significantly shortened overall survival. HFD reshaped the TME altering the lipid landscape, enhancing the CSC phenotype, stimulating tumor cell proliferation, and protecting from necrotic cell death. Similar results were not observed in metabolically obese, leptin-deficient ( ob/ob ) mice. We simultaneously identified a potent suppression of the gasotransmitter, hydrogen sulfide (H2 S). H2 S functions principally through protein S-sulfhydration and regulates multiple programs including bioenergetics, metabolism, and immune response. Inhibition of H2 S increased tumor cell proliferation and chemotherapy resistance, whereas treatment with H2 S donors reduced tumor cell fitness in vitro and attenuated GBM growth in vivo . Exogenous treatment with H2 S donors also rescued the lipid-mediated increase in tumor cell proliferation. As H2 S exerts its action though protein S-sulfhydration, we confirmed that HFD-fed mice, which experienced decreased H2 S synthesis, presented a severely depleted S-sulfhydrated protein landscape. Loss of this post-translational modification was confirmed in GBM patient tissues compared to age- and sex-matched controls. Taken together, our findings provide evidence that H2 S functions as a tumor suppressor in GBM. Our observations highlight a new mechanism for tumor growth dynamics that can be leveraged for new therapeutic strategies focused on boosting H2 S. Finally, our findings indicate that lifestyle factors can have pleiotropic effects on GBM progression through concomitant mechanisms involving tumor metabolism, modifications to the TME, and regulation over the CSC phenotype.